2019
DOI: 10.1177/1078390319865322
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Negative and Positive Mental Health Among Nursing Students in the United States

Abstract: BACKGROUND: Researchers have documented significant psychological problems among nursing students, but findings have been inconclusive as to whether nursing students are “at-risk” for mental health problems compared with their non-nursing peers. Aims: This study examined whether nursing students have unique mental health characteristics compared with students from other professions. METHOD: Undergraduates ( N = 18,312; nursing n = 1,399) were selected from the 2016-2017 National Healthy Minds Study. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
(46 reference statements)
4
15
0
1
Order By: Relevance
“…By contrast, although greater flourishing and belonging were robustly related to resilience and academic distress at the bivariate level (see Table 2), neither flourishing nor belonging were associated with negative academic impact when controlling for resilience or depression. Thus, our findings are consistent with numerous studies indicating that depression is particularly salient to academic well‐being (Beiter et al., 2015; Eisenberg, Hunt, & Speer, 2013; Hysenbegasi et al, 2005) and common among nursing students (McDermott et al., 2019; Tung et al., 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…By contrast, although greater flourishing and belonging were robustly related to resilience and academic distress at the bivariate level (see Table 2), neither flourishing nor belonging were associated with negative academic impact when controlling for resilience or depression. Thus, our findings are consistent with numerous studies indicating that depression is particularly salient to academic well‐being (Beiter et al., 2015; Eisenberg, Hunt, & Speer, 2013; Hysenbegasi et al, 2005) and common among nursing students (McDermott et al., 2019; Tung et al., 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Similar problems are evident in nursing school. McDermott et al (2019) recently found that approximately 20% of undergraduate nursing students across the United States screened positive for probable depression. For context, researchers at the National Center for Health Statistics estimated that the national prevalence rate of depression in the United States ranged from 5–11.5% (Brody, Pratt, & Hughes, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grit cannot be instantly learned or developed, but nursing students who are taught the importance of grit in school can cultivate this protective trait ( McCabe, 2016 ). Meanwhile, positive thinking like grit enables nursing students to overcome the stressful tasks associated with their nursing studies by fostering positive psychology that focuses on their inherent strengths ( McDermott et al, 2021 ). Students' emotional and psychological well-being is influenced by factors rooted in multiple sources, such as family and social environment, which impact their academic success.…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that female nursing students experience higher levels of stress than male nursing students 25 . In a study conducted with a large student population in the United States, female nursing students expressed higher levels of anxiety symptoms than female students in other professions 26 . In a study conducted with 1193 nursing students in Peru, ages between 20 and 29 years were a risk factor for both depression and anxiety, and being a woman was a risk factor for anxiety 27 .…”
Section: Discussionmentioning
confidence: 99%